Impact of visual distractors in virtual reality environments on sustained attention behavioral performance and EEG characteristics - Ai, Xiaowen; Wang, Yuhao; Wang, Peng; Wang, Suogang (Frontiers in Human Neuroscience, 2025)
IntroductionThis study investigates the effects of visual distractors in virtual reality (VR) environments on sustained attention, focusing on how visual distraction modulates neural mechanisms of attentional allocation and regulation.MethodsBehavioral and electroencephalographic (EEG) data were collected from 66 participants performing a Go/No-go continuous performance test (CPT) in a virtual classroom under conditions with (Y-D) and without (N-D) visual distractors. We analyzed behavioral performance (commission/omission errors, multipress, reaction time), event-related potential (P300) characteristics (latency, amplitude), and nonlinear dynamics (sample entropy, fuzzy entropy) of the EEG signals.ResultsBehavioral results revealed that visual distractors significantly increased commission errors, omission errors, and multipress (all p < 0.001), with no significant difference in reaction time. EEG analysis demonstrated that distractors significantly prolonged P300 latency, particularly at CPz, Pz, and Oz electrodes, and increased P300 amplitude at Fz, FCz, and Oz. Furthermore, both sample entropy and fuzzy entropy values were significantly higher under distraction conditions in the frontal, central, and parietal regions.DiscussionThese findings indicate that visual distractors disrupt cognitive processes related to visual information integration, attentional control, and decision-making, leading to decreased behavioral performance and increased neural complexity. This study deepens the understanding of the neural mechanisms of attention processing under ecological conditions and provides a scientific basis for optimizing educational environments and developing attention assessment tools based on neuroengineering.